The Association of Psychological Well‐Being with Disablement Processes in a National Sample. Issue 2 (5th February 2019) - Mishra, Aura Ankita; Friedman, Elliot M.; Christ, Sharon L.; Denning, Madison
Abstract : Objective: Objectives were to explore subgroups of individuals with differential disability trajectories and evaluate the protective effects of psychological well‐being (i.e. hedonic and eudaimonic) in the presence of multiple disease conditions (or multimorbidity) and sociodemographic disadvantages. Methods: Data come from the prospective longitudinal cohort study the Midlife Development in the United States ( n  =   3, 904). Three waves of data spanning a 20‐year period were used to identify subgroups with different disability trajectories. Subgroup membership was then modelled as a function of psychological well‐being assessed at wave 1 of the study using multinomial logistic regression. Results: Three unique groups were identified: a normative group with initially low and slowly increasing levels of disability; a group with high levels of disability that was stable over time; and a group with moderate initial levels of disability that increased over time. Hedonic well‐being at wave 1 was associated with membership in the risk groups relative to the normative group. Conclusion: Individuals may follow one of three disability pathways mostly as a function of multimorbidity. However, hedonic well‐being was associated with having an advantageous disability trajectory regardless of multimorbidity status. Cultivating psychological well‐being may improve disability outcomes in aging individuals.